Swedish Adolescents With Impairments Showed Lower Levels of Physical Activity, Fitness and Sports Participation - Kjellenberg, Karin (ohn Wiley & Sons Ltd, 2026)
Aim: Evidence on physical activity (PA), sedentary time, and fitness in adolescents with impairments has been limited. We aimed to compare outcomes in Swedish adolescents with and without impairments and between impairment types.
Methods: This cross-sectional study, from September to December 2019, comprised of adolescents from 34 mainstream schools within 3 h' drive of Stockholm, Sweden. Parents reported impairment status. PA and sedentary time were measured with accelerometers during school and leisure time on weekdays and weekends. Fitness was estimated using the Ekblom-Bak submaximal cycle test, sports participation was self-reported and multilevel mixed models were used for analyses.
Results: We enrolled 972 adolescents (51% girls), with a mean age of 13.4 ± 0.3 years. Just under a third (31%) had impairments. Adolescents with impairments showed lower PA levels, less adherence to recommendations, lower fitness and less participation in organised sports than those without impairments. Those with learning or visual impairments engaged in less vigorous activity and the former had lower fitness levels.
Conclusion: Adolescents with impairments were less physically active, more sedentary and had lower fitness than peers without impairments. This emphasises the need for equitable opportunities for PA, to support long-term health and well-being in adolescents with impairments.